2020
DOI: 10.1590/rbce.42.2019.278
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-time physical activity as a protective factor for functional capacity loss in community dwelling elders

Abstract: Populational aging led to the emergence of chronic diseases, all potentially incapacitating, thus affecting functional capacity (FC) of elders. Despite health evidences in favour of having regular physical activity, the majority of elders are not sufficiently active. Baseline data of an urban elder cohort in Brazil showed that only 28% were active and 68% had some functional loss, a figure that went up to 73% among the inactives. FC was associated with a network of sociodemographic, health and behavioral facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
8
25
0
7
Order By: Relevance
“…The bibliographic review carried out by Jensen and Hsiao (2010) (39) found that, in addition to being strongly related to BMI, FC is also related to involuntary changes in body weight, up or down. The reduction in FC with advancing age, as pointed out in this study, is consistently reported in the literature (8,11,14,16,40,42,(45)(46) . This relationship is explained by the discrete and constant biological and functional losses characteristic of the aging process that, even if not linear, are associated with age (47) .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The bibliographic review carried out by Jensen and Hsiao (2010) (39) found that, in addition to being strongly related to BMI, FC is also related to involuntary changes in body weight, up or down. The reduction in FC with advancing age, as pointed out in this study, is consistently reported in the literature (8,11,14,16,40,42,(45)(46) . This relationship is explained by the discrete and constant biological and functional losses characteristic of the aging process that, even if not linear, are associated with age (47) .…”
Section: Discussionsupporting
confidence: 88%
“…Studies relating LTPA and FC in aged people have in general a cross-sectional design (8,10,12,36) . Our longitudinal design enabled to explore the effect of LTPA on FC over a period of 3,5 years, controlling for all the other risk factors, providing estimates of the risk of changing FC due to the amount of LTPA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations